Aspectos institucionais da unificação das polícias no Brasil - Afonso Mateus Medeiros (Universidade do Estado do Rio de Janeiro, 2004)
This paper discusses the unification of the Brazilian military and civilian police forces, concentrating the empirical references from previous studies on the police forces in the States of São Paulo, Minas Gerais, and Rio de Janeiro. The approach does not focus on the efficiency of such a strategy in terms of crime control. Rather, the main preoccupation is with its legitimacy, as understood by the theory of organizations. Especially useful for this purpose is the concept of institutional field. The conclusion is that there is an incomplete institutionalization of the police field in Brazil. Throughout history, police forces have responded mostly to institutional demands from other fields, notably those of justice and defense. From this perspective, the unification proposal can be understood as an attempt to transform the nature of institutional demands directed towards police organizations.